Liquid waste service agreement between Tamale Metropolitan Assembly and private sanitation service providers is ensuring safely managed sanitation services for communities living in Tamale Metropolitan Assembly, Ghana - CGIAR Research Program on Water, Land and Ecosystems (2021)
WLE/IWMI brokered an agreement to ensure that the firms desludging septic tanks dispose of it safely